Pregnancy with adnexal masses: an institutional experience and review of the literature - Bahadur, Anupama; Sri, Modalavalasa Swetha; Mundhra, Rajlaxmi; Chawla, Latika; Ajmani, Megha; Afreen, Tuba; Kumari, Payal; Sharma, Shloka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Adnexal masses in pregnancy are not uncommon. We prospectively analysed all cases with adnexal masses detected during pregnancy presented to our antenatal outpatient department from January 2019 to August 2020. Herein we report six such cases with their pregnancy outcome. Among the 6 cases, 3 were diagnosed during first trimester of pregnancy, 2 in third trimester and 1 was found incidentally during caesarean section. The mean age of the cases was 25.33+2.33 years. Two cases underwent oophorectomy and rest had ovarian cystectomy. In terms of histopathological findings, one was endometriotic cyst, two were borderline tumors (mucinous and serous variety) and three were mature cystic teratomas. There was no perinatal mortality, but 2 babies required NICU admission for observation. Mature cystic teratoma was the most common adnexal mass detected in our series. Timing of surgery depends on urgency of situation. Asymptomatic/small/unilocular cyst with low suspicion should be kept under observation and follow up throughout pregnancy.